Investigating Skills-Based Language Assessment Literacy of EFL Teachers in Indonesia - ., Wiyaka; Fani Prastikawati, Entika; Yosephin Widarti Lestari, Maria; Mokhtar, Mahani (KnE Social Sciences, 2024)
As English as a Foreign Language (EFL) teachers, they must possess a sufficient understanding of assessment-related processes. Hence, it is critical to investigate the language assessment expertise possessed by language instructors as an initial measure towards developing language assessment literacy, to identify their proficiencies and limitations in the field of language assessment. To fill the gaps, this current study examines the level of language assessment knowledge among EFL teachers in higher education schools in Indonesia. This study employed the survey method and utilized 60 adopted items, consisting of four constructs. The study was conducted among a sample of 114 EFL teachers employed in both private and public schools in Indonesia. The statistical analysis indicated that, on average, the teachers’ level of language assessment knowledge is at a certain level. The findings of a one-sample t-test indicated a statistically significant difference between the scores obtained by teachers on the scale and half of the overall score. Additionally, the study revealed that the teachers demonstrated the highest level of expertise in evaluating reading skills, while their proficiency in assessing listening skills was comparatively lower. In conclusion, the current study provides several recommendations for both future research endeavors and policymakers in order to enhance the language assessment literacy of EFL instructors in evaluating individual language skills. Keywords: skills-based language assessment, language assessment literacy, EFL teachers